Mídia & religião: das portas da Igreja do castelo de Wittenberg aos processos de midiatização religiosa: desafios teológicos e pastorais diante das novas ambiências da palavra - Budke, Sidnei (2015)
The Christian religion is experiencing a new scenario, a new era, a transition described in multiple ways: the era of globalization , the era of information , the era of the network , the era of the media . Limiting ourselves to a scenario of globalization, of dilution of geographical and cultural boundaries, and of broad technological growth, one can identify a new hermeneutics in theological thinking: the mediatization of human religiosity. This still confused process spreads rapidly in the cultural diversity, breaks barriers of specific beliefs and stimulates new conceptions of spirituality. The goal of this thesis is to gather together theological and interdisciplinary studies related to Christianity and its involvement with the different processes of religious mediatization. The author establishes connections between the contemporary theoretical referentials and the ecclesiological thinking of Martin Luther when he points out that: it is necessary to recognize the Church not only in the condition of being passive regarding the interferences of the mediatization processes, but also as protagonist of a variety of ambiances of human and religious communication.